Cosmic ray observation at Syowa station in the Antarctic -- current status and near future plan -- - Kato, Chihiro; Miyake, Shoko; Hayashi, Yuki; Kataoka, Ryuho; Kozai, Masayoshi; Kadokura, Akira; Masuda, Yoshiki; Matsumoto, Mizuki (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OS] Space and upper atmospheric sciences, Wed. 15 Nov. / 3F Multipurpose Conference room, Institute of Statistical Mathematics conference object